Reorientalizing Islam: Terrorism and Discourse on Evil - Frans Fikki Djalong (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
The central point of this article discusses the liberal fundamentalist movements that operate and establish our current preoccupation with terrorism and its intriguing connections to Islam. Many of the proposed argument refers to the political thought of post-foundationalist which has a core focus on the ways in which Islam is widely regarded as a threat to the power of liberal order and global security. Rather than focusing on the perpetrators of terror actions or radical Muslim activists, this article takes a radically different route in making sense of the hegemonic construction of contemporary terrorism. The thesis of this paper states that Islam is the main target of the current discourse on terrorism. Liberal fundamentalism has sought to re-orientalize Islam through war and global projects of de-radicalization. In this discourse, the relationship between Islam, politics and violence is at stake.